Answer:
First, remember the conservation of energy.
We can define the kinetic energy as:
K = (1/2)*m*v^2
where m is the mass, and v is the velocity.
The velocity of the person is 6m/s, and the mass is unknown.
Now, when the person rides the skateboard, this kinetic energy must remain constant, if M is the mass of the skateboard, the speed after the person rides ir will be:
K' = (1/2)*(m + M)*v'^2
Where v' is the new velocity.
In this case, we can suppose that the skateboard has really small mass compared with the person.
M < < m
then:
(m + M) ≈ m
then:
K' = (1/2)*m*v'^2 = K = (1/2)*m*v^2
from that equation, we can conclude that:
v' = v
Then if the velocity before riding the skateboard was 6m/s, then after would be also 6m/s.